Mild Cognitive Impairment Is Not “Mild” at All in Altered Activation of Episodic Memory Brain Networks: Evidence from ALE Meta-Analysis - Wang, Pengyun; Li, Juan; Li, Hui-Jie; Huo, Lijuan; Li, Rui (Frontiers in Aging Neuroscience, 2016)
The present study conducted a quantitative meta-analysis aiming at assessing consensus across the functional neuroimaging studies of episodic memory in individuals with amnestic mild cognitive impairment (aMCI) and elucidating consistent activation patterns. An activation likelihood estimation (ALE) was conducted on the functional neuroimaging studies of episodic encoding and retrieval in aMCI individuals published up to March 31, 2015. Analyses covered 24 studies, which yielded 770 distinct foci. Compared to healthy controls, aMCI individuals showed statistically significant consistent activation differences in a widespread episodic memory network, not only in the bilateral medial temporal lobe and prefrontal cortex, but also in the angular gyrus, precunes, posterior cingulate cortex, and even certain more basic structures. The present ALE meta-analysis revealed that the abnormal patterns of widespread episodic memory network indicated that individuals with aMCI may not be completely “mild” in nature.